Action research for inclusive education : participation and democracy in teaching and learning - Armstrong, Felicity, 1966-; Tsokova, Diana (Routledge, Taylor & Francis Group, 2019)
"Exploring practitioner research and the possibilities it creates for increasing student participation and developing inclusive practices in educational contexts, this insightful text presents a range of original and innovative approaches to action research, and highlights the critical relationship between educational theory, research and practice in transformative action. Focussing on social constructivist approaches to teaching and learning, Action Research for Inclusive Education offers first-hand insights from researcher-practitioners from international settings including Denmark, Germany, Ireland, Saudi Arabia, Granada, Greece, Singapore and England. Chapters explore diverse participatory and collaborative research practices which draw on the strengths and contributions of teachers and support staff, pupils, and families to foster inclusive practices across the school community and strengthen the participation and independence of all students. Topics considered include collaboration in participatory action research, friendships and the development of students' social skills, student voice and the role of pupils as co-researchers and peer mentors. Making an important contribution to debates on inclusive education and the role of practitioners and students in bringing about change, this text will be key reading for students, teachers and educational researchers"--
Keywords: integrovaná výchova a vzdělávání; akční výzkum; integrated education; action research; kolektivní monografie; collective monographs